2016
DOI: 10.18632/oncotarget.10488
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase inhibitors regulate P-gp expression in colorectal cancer via transcriptional activation and mRNA stabilization

Abstract: Histone deacetylase inhibitors (HDACIs) are emerging as a novel class of anti-tumor drugs. But the effect of HDACIs in tumors treatment has been disappointing, which mainly due to the acquisition of resistance to HDACIs. However, the underlying mechanisms have not been clearly understood. In this study, it was found that HDACIs SAHA and TSA increased P-gp expression in CRC cells, which has been well known to contribute to drug resistant. The mechanisms underlying these effects were investigated. We showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 35 publications
2
13
0
Order By: Relevance
“…For instance, the HDAC inhibitors SAHA, TSA and phenylbutyrate were reported to increase ABCB1 expression in acute myeloid leukemia (29). Our previous study revealed that SAHA, TSA and sodium butyrate induced ABCB1 expression by transcriptional activation of STAT3, and stabilized ABCB1 mRNA in lung and colorectal cancer (22,23). Consistently, the present study also demonstrated that SAHA and TSA significantly increase ABCB1 mRNA and protein expression in A549 and HCT116 cells.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…For instance, the HDAC inhibitors SAHA, TSA and phenylbutyrate were reported to increase ABCB1 expression in acute myeloid leukemia (29). Our previous study revealed that SAHA, TSA and sodium butyrate induced ABCB1 expression by transcriptional activation of STAT3, and stabilized ABCB1 mRNA in lung and colorectal cancer (22,23). Consistently, the present study also demonstrated that SAHA and TSA significantly increase ABCB1 mRNA and protein expression in A549 and HCT116 cells.…”
Section: Discussionsupporting
confidence: 89%
“…Our previous study and other previous research have demonstrated that treatment of cancer cells with HDAC inhibitors increases the expression of ABCB1, which results in the development of an MDR phenotype (22,23). However, the effects of HDAC inhibitors on other MDR-associated ABC transporters have not previously been reported.…”
Section: Introductionmentioning
confidence: 83%
“…These studies have since been repeated using different HDAC inhibitors. SAHA and TSA upregulated P-gp expression in HCT116 colorectal cancer cells within 25 h of exposure [114]. P-gp expression was upregulated at two different steps, translational initiation and mRNA stabilization [115], and HDAC inhibitors increase P-gp expression in both stages [115].…”
Section: P-glycoproteinmentioning
confidence: 96%
“…In this study, we assessed the mechanism through which ivermectin regulates YAP1 function for the first time and demonstrated that ivermectin decreased YAP1 mRNA expression, resulting in reduced nuclear expression of YAP1 protein in GC cells (Figure 5B ). Ivermectin-induced YAP1 mRNA downregulation was assumed to occur through transcriptional inactivation or mRNA destabilization [ 19 ]. Further experiments are required to clarify this mechanism.…”
Section: Discussionmentioning
confidence: 99%